A Novel Identified Long Non-coding RNA, lncRNA MEF2C-AS1, Inhibits Cervical Cancer via Regulation of miR-592/RSPO1 - Wang, Xiaoping; Zhang, Changhong; Gong, Meixuan; Jiang, Chen (Frontiers in Molecular Biosciences, 2021)
Purpose: Our purpose was to investigate the effect of lncRNA MEF2C antisense RNA 1 (MEF2C-AS1) on cervical cancer (CC), and further explore its underlying molecular mechanisms. Methods: The proliferation, migration and invasion of CC cells were determined by counting Kit-8 (CCK-8), colony formation assay, and transwell assays, respectively. qRT-PCR and western blot were conducted to quantitatively detect the expression of lncRNA MEF2C-AS1, miR-592 and R-spondin1 (RSPO1). Kaplan-Meier survival curve from the Cancer Genome Atlas (TCGA) database and the Gene Expression Profiling Interactive Analysis (GEPIA) website was used to describe the overall survival. Bioinformatics analysis was performed to search the downstream target of lncRNA MEF2C-AS1 and miR-592. Luciferase reporter assay was conducted to detect the interaction between lncRNA MEF2C-AS1 and miR-592 or miR-592 and RSPO1. Results: The data from GEPIA website showed that lncRNA MEF2C-AS1 expression was down-regulated in CC tissues and also associated with survival rate of CC patients. Moreover, the results of qRT-PCR also showed lncRNA MEF2C-AS1 was lowly expressed in CC cells. Subsequently, we confirmed that overexpression of lncRNA MEF2C-AS1 inhibited the proliferation, migration and invasion of CC cells. Further research illustrated that lncRNA MEF2C-AS1 was the target of miR-592, and RSPO1 was the downstream target gene of miR-592. Importantly, functional research findings indicated that lncRNA MEF2C-AS1 inhibited CC via suppressing miR-592 by targeting RSPO1. Conclusions: In our study, we demonstrated the functional role of the lncRNA MEF2C-AS1-miR-592-RSPO1 axis in the progression of CC, which provides a latent target for CC treatment.